The influence of parents and coach’s roles on character building in 18 years junior tennis athlete - Ngatman Ngatman; Hendra Setyawan; Ismail Gani; Ari Iswanto; Dennis Dwi Kurniawan; Willy Ihsan Rizkyanto; Zainudin Abu Bakar (Jurnal Keolahragaan, 2023)
This study aims to determine the effect of the role of parents and coaches on the character of junior tennis players in Special Region of Yogyakarta (DIY). This research is a correlational study using a quantitative approach. Data colection techniques using a questionnaire. The sample for this study consisted of 32 junior tennis respondents in DIY using a purposive sampling technique. The reliability and validity of the instruments used in this study have been examined, and experts have been consulted. Technique for data analysis based on multiple regression. Based on the results of the t-test analysis, the significant value of the variable role of parents is p 0.05 and coaches is p 0.05. This shows that partially the role of parents and coaches influences the character of DIY junior tennis players. Using the F test, the analysis yielded a significance level of p less than 0.05, while the value of Rsquare=0.719, meaning that 71.9% of the characteristics of DIY junior tennis players are influenced by the role of parents and coaches. Thus, it can be concluded that the roles of parents and coaches simultaneously have an influence on the character of DIY junior tennis players. Therefore, in providing character education to junior tennis players both inside and outside the field, external encouragement is needed, both from parents and coaches.